Radiotherapy Combined With Concurrent Nedaplatin-Based Chemotherapy for Stage II-III Esophageal Squamous Cell Carcinoma - Huiping Zhu MD; Xiaoling Lu MS; Jian Jiang MS; Jingfeng Lu MS; Xinchen Sun PhD, MD; Yun Zuo PhD, MD (SAGE Publishing, 2022)
Objective This study was conducted to explore the appropriate radical radiation dose in concurrent chemoradiotherapy (CCRT) for patients with inoperable stage II-III esophageal squamous cell carcinoma (ESCC). Methods This retrospective study included patients with esophageal cancer (EC) from the database of patients treated at the Affiliated Zhangjiagang Hospital of Soochow University (1/2015-12/2019). Overall survival (OS), progression-free survival (PFS), objective remission rate (ORR), first failure pattern, and toxicities were collected. Results 112 patients treated with intensity-modulated radiation therapy (IMRT) combined with concurrent chemotherapy of nedaplatin-based regimens were included. Fifty-eight (51.8%) and 54 (48.2%) patients received 60 (HD) and 50.4 (LD) Gy of radiotherapy, respectively. The HD group showed superior OS and a trend for longer PFS compared with the LD group (median OS: 25.5 vs 17.5 months, P = .021; median PFS: 14.0 vs 10.5 months, P = .076). There were more patients with a complete remission (CR) in the HD group than in the LD group (P=.016). The treatment-related toxicities were generally acceptable, but HD radiotherapy would increase the incidence of grade ≥3 late radiotoxicity (22.4% vs 5.6%, P = .011). Conclusion In nedaplatin-based CCRT for stage II-III ESCC, the radiotherapy dose of 60 Gy achieved a better prognosis. Strengths and limitations of this study A comparative study of 50.4 Gy and 60 Gy was conducted to evaluate whether 50.4 Gy can be used as a radical radiotherapy dose for inoperable stage II-III esophageal squamous cell carcinoma from a real-world perspective. The highly consistent selection criteria in our study make analysis results highly reliable and scientific. The existing research results support that nedaplatin can be used in concurrent chemoradiotherapy for esophageal squamous cell carcinoma, and this study focuses on the discovery of a better nedaplatin-based combination regimen. The findings of this study are limited to a single-center study with a non-large sample size. Inevitably, recall bias may exist in this retrospective study. Surgery was not involved in the follow-up treatment after concurrent chemoradiotherapy, which may worsen the prognosis of some patients.